Animal factors affecting the cheese-making properties and the heat coagulation time of milk from dairy sheep in a New Zealand flock - Marshall AC; Lopez-Villalobos N; Loveday SM; Weeks M; McNabb W (Taylor and Francis Group on behalf of the Royal Society of New Zealand, 2024)
The objective of this study was to evaluate the effect of animal factors on the cheese-making properties and on the heat coagulation time of milk from individual dairy sheep in a New Zealand flock. A total of 521 individual records were obtained from a seasonal pasture-based flock of 169 ewes milked once-a-day, from 50 to 182 days in milk. A statistical model was used to quantify the effects of animal factors (coat colour variety, age, litter size and stage of lactation) on the studied traits. Stage of lactation, confounded with seasonality, strongly influenced all properties of milk investigated. With the advancement of lactation, the milk took longer to coagulate after rennet addition, and the curd was softer. Higher relative cheese yield was achieved towards the end of lactation. The milk was also less stable to high-temperature treatment in late lactation. Coefficient of variation for processability traits was high and ranged from 20.2% to 58%, which can be largely attributed to stage of lactation but could also indicate room for genetic improvement of traits. Further genetic studies are underway to define animal genetic variance, heritability, and the phenotypic and genetic correlations between these processability and milk composition traits.
Keywords: Milk coagulation; cheese yield; heat coagulation time; milk composition; dairy sheep; stage of lactation; seasonal